Effect of fructooligosaccharides on the physicochemical properties of sour cassava starch and baking quality of gluten-free cheese bread - Rodriguez-Sandoval, Eduardo (2014)
The present research was undertaken to explore the influence of fructooligosaccharides (FOS) on the functional and thermal properties of sour cassava starch and the quality characteristics of gluten-free (GF) cheese bread. Fructooligosaccharides were used to replace sour cassava starch at substitution level of 9% (SF1), 17% (SF2), and 29% (SF3). The functional and thermal properties of the starch-FOS mixtures were determined by the water absorption index (WAI), water solubility index (WSI), pasting profile analysis, thermal transition temperatures and enthalpy of gelatinization. Moreover, the GF cheese breads with starch-FOS mixtures were analyzed for height, diameter, weight, specific volume and dough moisture content. The sample with the highest FOS content (SF3) presented the lowest WAI (1.44), peak (62.4 rapid visco units (RVU), breakdown (53.4 RVU), final (13.8 RVU), and setback (4.9 RVU) viscosities, dough moisture content (31.7%), and enthalpy of gelatinization (9.5 J/g) and the highest WSI (29.4%) and pasting temperature (69.1 degrees C). The height, diameter and specific volume of GF cheese bread samples made from sour cassava starch were 3.14 cm, 6.35 cm, and 1.49 cm(3)/g, respectively. The SF1 mixture samples resulted in a 3.01 cm height, 6.34 cm diameter, and 1.55 cm(3)/g specific volume. According to Brazilian food labeling regulations, the latter product cannot be categorized as a good source of fiber because the minimum level of fiber per portion was not reached.